Q: What is the factorization of -4x2 plus 11x-6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4x2 + 12x + 5 = (2x + 1)(2x + 5).

It is: -4x^2 +11x -6 equals (-4x+3)(x-2) when factored

4x2 plus 3=11

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

x3 + 4x2 + 6x + 24 = (x2 + 6)(x + 4)

Related questions

4x2 + 12x + 5 = (2x + 1)(2x + 5).

2(x + 1)(2x + 1)

Divide all terms by 4:- x2+7x+12 = (x+3)(x+4) when factored

It is: -4x^2 +11x -6 equals (-4x+3)(x-2) when factored

4x2 plus 3=11

y=4x2+3x+8

4x2 + x2 = 8 + x2

4x2+20x+25 (2x+5)^2

X3 - 4X2 - 45XX(X2 - 4X - 45)=============X is only common factor here.

2(x + 1)(2x + 1)

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

4x^2 + 32x + 64 = 4(x^2 + 8x + 16) = 4(x + 4)^2 = 4(x + 4)(x + 4)